Iron supplementation and deworming during pregnancy reduces the risk of anemia and stunting in infants less than 2 years of age: a study from Sub-Saharan Africa - Stanislav Seydou Traore; Yacong Bo; Guangning Kou; Quanjun Lyu (BMC, 2023)
Abstract Background In sub-Saharan Africa, infant anemia, stunting and low birth weight remains major public health problems. It is unclear whether prenatal iron supplementation and/or deworming can reduce the risk of infant stunting, anemia and low birth weight. The aim of this study was to investigate the relationship between iron supplementation and/or deworming and stunting, anemia, and low birth weight in infants under two years of age in sub-Saharan Africa. Methods Our studies examined pooled data from Demographic and Health Surveys (DHS) in twenty-three African countries collected between 2014 and 2020. childhood anemia and stunting in infants under the age of two were the primary outcomes. Iron supplementation and deworming during prenatal visits were the main exposure variables. A multivariate logistic regression model was used to investigate these relationships. Results The prevalence of stunting was 29.9%, severe stunting was 10.6%, childhood anemia was 74.3%, childhood severe anemia was 3.2%, and low birth weight was 16.4%, respectively. The use of prenatal iron supplementation alone was associated with a significant reduction of childhood anemia [aOR (95% CI) = 0.9 (0.8-1.0)]. Prenatal deworming alone was associated with a significantly reduced risk of stunting [aOR (95% CI) = 0.7 (0.8-1.0)], childhood anemia [aOR (95% CI) = 0.7 (0.8-0.9)], and low birth weight [aOR (95% CI) = 0.7 (0.8-1.0)]. Prenatal iron supplementation plus deworming or iron supplementation (with or without deworming) were not associated with childhood anemia, infant stunting and low birth weight. Conclusions In Sub-Saharan Africa, prenatal deworming alone has the potential to improve infants' outcomes. Childhood anemia was improved with prenatal iron supplementation alone. Our recent findings indicate the necessity for prospective studies on the association between prenatal iron supplementation plus deworming and childhood anemia, stunting and low birth weight.